Corrosion Control of Metal Alloy Using Inhibitor Synergy: Phospate – Carbohydrazide - Fachrul Nurcholis; Aditya Irfansyah; Isni Utami; Lilik Suprianti (Future Science, 2022)
Stainless steel is a kind of metal alloy that is widely used in industrial equipment. The problem faced by all metals that come into contact with corrosive medium is corrosion. Corrosion or metal deterioration can not be avoided since it is a spontaneous reaction between the metal with its environment. One method to control the corrosion of metal alloy is by adding the inhibitor into the medium. The addition of inhibitors in synergy is discussed. The addition of a phosphate inhibitor as a film-forming role on the metal surface is assisted by the addition of carbohydrazide components in controlling dissolved oxygen levels in seawater. The addition of inhibitors in synergy is expected to increase the efficiency of the inhibitor’s performance in a single work. This research aims to determine the best composition for phosphate and carbohydrazide inhibitors due to the effect of synergy in controlling the corrosion rate of metal alloys in seawater. The synthetic seawater medium was the 3.5% NaCl dilution prepared by diluting the NaCl crystal into the demineralized water. The phosphate inhibitor was added into the medium with various compositions (100, 200, 300, 400, and 500 ppm). Then, the carbohydrazide was added into the medium with the multiple compositions 5, 7.5, 10 and 15. The corrosion rate measurement was done by using Electrochemical Impedance Spectroscopy Instrument. The Stainless steel sample was prepared by cutting the stainless steel plate with a size 1cm x 1 cm and a thickness of around 2- 3 mm. The measurement process was done by putting the specimen in the working electrode and dipping into the medium with and without the inhibitors. The results show that the addition of inhibitor effectively decreases the corrosion rate. The best result is obtained when the ratio between phosphate and carbohydrazide is 100:10 ppm, which reduces the corrosion rate from 0.40128 mpy to 0.008 mpy